Odpowiedzi

2009-12-16T22:12:41+01:00
A)

{5y+5=x+3y
{5y+5=2x

{5y-3y-x=-5
{5y-2x=-5

{2y-x=-5 <--- mnożymy *-2
{5y-2x=-5

{-4y+2x=+10
{5y-2x=-5

y=10-5
y=5

a skoro y=5
2y-x=-5
10-x=-5
-x=-15
x=15


b)

{2c-3d=c-5
{c-d=15

{2c-c-3d=-5
{c-d=15

{c-3d=-5 <mnozymy *-1
{c-d=15

{3d-c=5
{-d+c=15 (c się skraca)

2d=15+5
2d=20 //2
d=10

c-d=15
c=15+d
c=25
2009-12-16T22:16:01+01:00
5y+5=x+3y
5y+5=2x

2y-x=5 /*-2
5y-2x=-5

-4y+2x=-10
5y-2x=-5

y=-15
5*(-15)-2x=-5
-65-2x=-5
-2x=-5+65
-2x=60
x=-30

b)
2c-3d=c-5
c-d=15

c-3d=-5
c-d=15

-c+3d=5
c-d=15

2d=20
d=10
c-10=15
c=15+10
c=25
2009-12-16T22:16:30+01:00
5y+5=x+3
5y+5=2x odemujesz stronami
wychodzi
0=-x+3 gdzie x=3